Ecological Stoichiometric Characteristics of Plant–Litter–Soil Among Different Forest Stands in a Limestone Region of China - Yeqiao Wang; Haochuan Tu; Jingjing Zheng; Xiongjie Li; Guibin Wang; Jing Guo (Plants, 2025)
The transformation of degraded stands represents an essential strategy for enhancing stand productivity and optimizing site adaptability. This study examined four typical monoculture forest stands transformed from underperforming Platycladus orientalis (PO) forests in the limestone area of Xuzhou, China: Acer pictum subsp. mono (AP), Pistacia chinensis (PC), Ligustrum lucidum (LL), and Firmiana simplex (FS). The contents of carbon (C), nitrogen (N), and phosphorus (P), along with the C:N:P stoichiometric ratios, were analyzed in plants (leaves and fine roots), litter, and soil. The relationships among these components and their main influencing factors were explored. The results indicated that FS leaves contained higher levels of N and P, whereas LL litter presented significantly elevated C:N and N:P ratios in comparison with those of the other forest stands (p < 0.05). With the exception of FS, leaves displayed lower P than fine roots, which presented pronounced P enrichment. The soil C, N, and P contents decreased with depth, with both the forest stand and depth significantly impacting the soil stoichiometry (p < 0.01). Redundancy analysis identified available potassium, total nitrogen, and microbial biomass carbon in the soil as key factors influencing the stoichiometric characteristics of the leaf–fine root–litter continuum. Collectively, the leaf N:P ratios (>16) and low soil P contents indicate that plantation growth was primarily constrained by P limitation. In response, AP, PC, and LL allocate more P to fine roots to adapt to the environment.